Evidence-Based Training Recommendations for the Elite Judoka. Issue 2 (April 2019) - Harris, Dale M.; Foulds, Steven; Latella, Christopher
Abstract : ABSTRACT: THERE IS A PAUCITY OF SPORT-SPECIFIC EVIDENCE REGARDING STRENGTH AND CONDITIONING STRATEGIES TO IMPROVE ELITE JUDO ATHLETES' (EJA) PERFORMANCE. THEREFORE, THE AIM OF THIS ARTICLE IS TO EVALUATE THE CURRENT LITERATURE AND PRESENT EVIDENCE-BASED TRAINING RECOMMENDATIONS FOR EJA. BASED ON THE SPORT-SPECIFIC DEMANDS, APPROPRIATELY SEQUENCED PERIODIZED STRENGTH AND CONDITIONING PROGRAMS THAT INCLUDE (a) HEAVY STRENGTH TRAINING, (b) POWER TRAINING (i.e., CONTRAST LOADING, CLUSTER SETS, WEIGHTLIFTING, AND PLYOMETRIC EXERCISES), AND (c) HIGH-INTENSITY INTERVAL TRAINING MAY PROVIDE SUFFICIENT STIMULI TO IMPROVE UPPER- AND LOWER-BODY STRENGTH, AEROBIC AND ANAEROBIC POWER FOR EJA.